Isolation and molecular characterization of dissolved organic phosphorus using electrodialysis‐reverse osmosis and solution 31P‐NMR. (13th February 2017) - Bell, Douglas W.; Pellechia, Perry; Chambers, Luke R.; Longo, Amelia F.; McCabe, Kelly M.; Ingall, Ellery D.; Benitez‐Nelson, Claudia R.
Abstract: The composition of dissolved organic phosphorus (DOP), which directly impacts its biological and chemical reactivity, remains poorly constrained due to methodological and operational challenges. A series of compound‐specific isolation experiments and bulk estuarine seawater isolations were conducted to assess the ability of coupled electrodialysis (ED) and reverse osmosis (RO) to isolate DOP from seawater for molecular characterization using solution 31 P‐NMR analysis. These isolations were carried out using a recently developed small‐volume (24 L) ED/RO system. Compound‐specific isolation experiments ( n = 7) averaged 64.1% ± 9.2% for final DOP recovery, while recoveries for estuarine seawater ( n = 7) were on average 83.8% ± 10.7%. Nearly complete mass balance of DOP was observed for the compound‐specific isolations (88.1% ± 11.2%) with ED responsible for the majority of DOP loss (16% ± 5%). Isolation recovery was impacted by compound molecular weight rather than charge‐to‐size ratio. Isolation bias between bulk dissolved organic carbon and DOP was negligible. Solution 31 P‐NMR confirmed that ED/RO isolation does not impact molecular integrity or DOP composition. In addition, solution 31 P‐NMR accurately estimated several components (phosphonomethyl‐glycine, D‐glucose‐6‐phosphate, L‐ α ‐phosphatidylcholine) of an artificial complex DOP matrix. However, we suggest further refinements for ED/RO operation and significant caveats remain for 31 P‐NMR sample preparation and the interpretation of 31 P‐NMR spectra. Hydrolysis from NaOH dissolution was found to impact the ability to accurately resolve diester composition (ca. 40% underestimation) and discrimination between terminal and central phosphoanhydride atoms. Nonetheless, our results describe a viable option for the isolation and molecular characterization of marine DOP.